Effects of different thermal processing methods on bioactive components, phenolic compounds, and antioxidant activities of Qingke (highland hull-less barley) - Qingyue Hong; Guangjing Chen; Zhirong Wang; Xuhui Chen; Jianquan Kan (Food Science and Human Wellness)
Qingke (highland hull-less barley) is a grain replete with substantial nutrients and bioactive ingredients. In this study, we evaluated the effects of boiling (BO), steaming (ST), microwave baking (MB), far-infrared baking (FB), steam explosion (SE), and deep frying (DF) on bioactive components, phenolic compounds, and antioxidant activities of Qingke compared with the effects of traditional roast (TR). Results showed that the soluble dietary fiber, beta-glucan and water-extractable pentosans of Qingke in dry heat processes of TR, SE, MB and FB had a higher content compared with other thermal methods and had a better antioxidant activity of hydroxyl radical scavenging and a better reduction capacity, while those in wet heat processes of BO and ST had a better antioxidant activity of ABTS radical scavenging and a better Fe2+ chelating ability. DF- and SE-Qingke had a higher content of tocopherol, phenolic, and flavonoid. Overall, 6 free phenolic compounds and 12 bound phenolic compounds of Qingke were identified, and free phenolic compounds suffered more damage during thermal processing. Principal component analysis showed that SE had more advantages in retaining and improving the main biological active ingredients of Qingke, and it may be the best method for treating Qingke.